Successional patterns along soil development gradients formed by glacier retreat in the Maritime Antarctic, King George Island - Boy, Jens; Godoy, Roberto; Shibistova, Olga; Boy, Diana; McCulloch, Robert; De La Fuente, Alberto Andrino; Morales, Mauricio Aguirre; Mikutta, Robert; Guggenberger, Georg (Santiago : Sociedad de Biologia de Chile, 2016)
Background: Maritime Antarctica is severely affected by climate change and accelerating glacier retreat forming temporal gradients of soil development. Successional patterns of soil development and plant succession in the region are largely unknown, as are the feedback mechanisms between both processes. Here we identify three temporal gradients representing horizontal and vertical glacier retreat, as well as formation of raised beaches due to isostatic uplift, and describe soil formation and plant succession along them. Our hypotheses are (i) plants in Antarctica are able to modulate the two base parameters in soil development, organic C content and pH, along the temporal gradients, leading to an increase in organic carbon and soil acidity at relatively short time scales, (ii) the soil development induces succession along these gradients, and (iii) with increasing soil development, bryophytes and Deschampsia antarctica develop mycorrhiza in maritime Antarctica in order to foster interaction with soil. Results: All temporal gradients showed soil development leading to differentiation of soil horizons, carbon accumulation and increasing pH with age. Photoautptroph succession occurred rapidly after glacier retreat, but occurrences of mosses and lichens interacting with soils by rhizoids or rhizines were only observed in the later stages. The community of ground dwelling mosses and lichens is the climax community of soil succession, as the Antarctic hairgrass D. antarctica was restricted to ornithic soils. Neither D. antarctica nor mosses at the best developed soils showed any sign of mycorrhization. Conclusion: Temporal gradients formed by glacier retreat can be identified in maritime Antarctic, where soil development and plant succession of a remarkable pace can be observed, although pseudo-succession occurs by fertilization gradients caused by bird feces. Thus, the majority of ice-free surface in Antarctica is colonized by plant communities which interact with soil by litter input rather than by direct transfer of photoassimilates to soil.